KEDUDUKAN DAN HAK KREDITUR DALAM PROSES PKPU PASCA PUTUSAN PENGADILAN - Hanafie, Nurharsya Khaer; Firmansyah, Firmansyah; Akmasari, Nanda Mayada; Fortuna, Dewi (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2024)
Postponement of Debt Payment Obligations (PKPU) is a legal mechanism that allows debtors to restructure based on approval from creditors. based on the Bankruptcy Law and PKPU, provides legal protection to creditors during the debt restructuring process. This article examines in depth the position and rights of creditors during the PKPU process and after the court decision. The research method uses a normative juridical approach to provide descriptive descriptions based on legal literature, statutory regulations and related court decisions. The research method used is a normative juridical approach with descriptive analysis of legal literature, legislation, and related court decisions. The research findings show that creditors have significant rights in the PKPU process, including the right to file a PKPU petition, the right to vote in creditor meetings, and the right to receive payments according to the agreed-upon settlement plan. Additionally, creditors have the right to demand the implementation of the settlement plan or receive a portion of the proceeds from the liquidation of the debtor's assets in the event of bankruptcy. However, the exercise of these rights often faces various challenges, such as delays in court proceedings, lack of transparency in the execution of the settlement plan, and legal uncertainties that may disadvantage creditors. The research concludes that although creditors' rights are clearly outlined in the law, practical implementation still shows gaps between theory and practice. Efforts are needed to enhance the efficiency of court processes and transparency in the execution of settlement plans to ensure optimal protection for creditors. Recommendations include improving the capacity of human resources in judicial institutions, implementing information technology to expedite administrative processes, and increasing oversight of settlement plan implementation. This article aims to contribute to the understanding and handling of issues related to the position and rights of creditors in the PKPU process, and serve as a reference for legal practitioners, academics, and stakeholders in the field of bankruptcy law and PKPU in Indonesia.